VIDEO-BASED LEARNING ON STATISTICAL TOPICS AMONG FOUNDATION STUDENTS IN UNIVERSITI MALAYSIA SABAH: AN IN-DEPTH ANALYSIS OF SATISFACTION - Nurliyana Juhan; Che Haziqah Che Hussin; Mohd Azrul Abdul Rajak; Sitty Nur Syafa Bakri, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Video-based learning has recently gained popularity as one of the numerous choices in remote education approaches during the pandemic that differs from conventional face-to-face lecture-based education. However, video-based learning and online teaching were different and quite challenging for students, especially when studying statistics and it is conducted remotely. Therefore, the purpose of this study is to assess student satisfaction with video-based learning on statistical topics. This study was conducted with 357 foundations of science students in the Preparatory Centre for Science and Technology, Universiti Malaysia Sabah. An independently developed questionnaire focusing on four factors, namely teaching, learning, technology, and skills, was given to students, and the results were then analysed. Based on the questionnaire the range of the mean is 4.54 – 4.87, which suggested that the video-based learning on statistical topics had an overall positive outcome on student satisfaction. Mostly, students scored higher mean scores for the items under the factor of teaching than for the items under the other three factors. This study also discovered that video-based learning relied on teaching, learning, and skills rather than the technology itself. However, technology continues to be a critical platform for educators’ educational activities. Therefore, this study demonstrated the critical significance of meeting the rising demand for online education, particularly video-based learning, while still providing a compelling student learning experience.